Beyond Copenhagen: REDD+, agriculture, adaptation strategies and poverty - Campbell, Bruce M. (Elsevier, 2009)
When negotiations began on the post-2012 global climate change regime, forests and forestry returned to the international stage (Angelsen, 2008). I ask whether it is the time now for agriculture, and whether climate change initiatives in forestry and agriculture can contribute to poverty alleviation efforts.